2021
DOI: 10.24191/jeeir.v9i1.12736
|View full text |Cite
|
Sign up to set email alerts
|

Influence of COVID-19's active cases on Malaysia's key economic performance indicators

Abstract: The COVID-19 outbreak was a rare and unprecedented phenomenon. Hence, the pandemic forces the world economy to react unpredictably. Governments worldwide have undertaken several precautions, including social distance measures, public awareness programs, policies on testing and quarantine, and financial aid packages. Using endogenous growth theory, this paper examines the impact of COVID-19 towards Malaysia key economic indicator's performance using univariate regression analysis based on daily time series data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In addition, the MCO harm the bottom line of the firms, then causing the stock prices to plunge at the earlier stage of COVID-19 outbreak (Chia et al, 2020). The previous findings also shown that the daily COVID-19 cases in the past posed a negative effect on the Malaysian stock market activities (Gamal et al, 2021) and other economic performance indicators (Mustaffa et al, 2021). In contrast, the death cases do not pose any significant impact on the Malaysian stock market movements (Chia et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 91%
“…In addition, the MCO harm the bottom line of the firms, then causing the stock prices to plunge at the earlier stage of COVID-19 outbreak (Chia et al, 2020). The previous findings also shown that the daily COVID-19 cases in the past posed a negative effect on the Malaysian stock market activities (Gamal et al, 2021) and other economic performance indicators (Mustaffa et al, 2021). In contrast, the death cases do not pose any significant impact on the Malaysian stock market movements (Chia et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 91%
“…Feng, Yang, Gong, and Chang (2021) indicated that an increase in COVID-19's confirmed cases does increase exchange rate volatility significantly. Mustaffa, Abidin, Ahmad, and Ogundare (2021) found that COVID-19 had a significant impact on the unemployment rate, GDP, CPI, foreign exchange rate, and equity price in Malaysia. Narayan, Devpura, and Wang (2020) showed that COVID-19 had caused the depreciation of the Yen against the US dollar and brought profits from Japanese stocks' returns.…”
Section: Existing Studiesmentioning
confidence: 99%
“…Many economists and academicians argued that the current outbreak would cause a short-term fiscal impact and long-term economic impact on the nation worldwide (Shang et al, 2021). The COVID-19 outbreak has required nearly all countries to implement movement restrictions or lockdowns that have resulted in the reduction in demand and supply (United Nations Industrial Development (UNIDO), 2020; Mustafa et al, 2021). This reduction in demand and supply has caused a recession within the economic system.…”
Section: The Impact Of Serious Diseases On Economic Structurementioning
confidence: 99%